Prototype of an Internet of Things-Based Irrigation System Using Soil Moisture Sensors for Monitoring Rice Field Drought in Lape Village - Yudi Mulyanto; Eri Sasmita Susanto; Syafira Gestiana; Yunanri W (Journal of Applied Informatics Science, 2026)
Water management in rice fields remained a challenge, especially during drought conditions caused by suboptimal manual irrigation systems. Inaccurate timing and water volume often led to insufficient water supply for crops. This study aimed to develop a prototype of an automatic irrigation system based on the Internet of Things using ESP32 and a fuzzy logic method to reduce the risk of drought. The system monitored field conditions and controlled irrigation automatically through a web-based platform by utilizing soil moisture sensors and ultrasonic sensors. The research method employed a quantitative experimental approach through system design and testing. The results showed that the system was capable of automatically controlling water gates and pumps based on fuzzy logic output, enabling precise irrigation. This system was expected to improve water use efficiency in rice fields.